Cog and God: A response to Anne Foerst. - Reich, K. Helmut (Zygon: Journal of Religion & Science)
Presents a paper which responds to the essay titled `Cog, a Humanoid Robot, and the Question of the Image of God,' by Anne Foerst. Assesment of Cog's arguments on embodied artificial intelligence (AI) and the religion-science dialogue; Theologians perspective of the human person; Symbolic description of human beings in AI.